CHARACTERISTICS OF BLOOD DONORS, ACCORDING TO THE RESULTS OF COMPLEX LABORATORY TESTS OF PERIFERAL BLOOD - Oksana Muliarchuk; Stanislav Vydyborets (Scientific Journal of Polonia University, 2022)
Nowadays, there is a significant storage of donated blood in the world. According to the recommendations of the WHO, adequate and reliable supply of save donated blood can only by carried out on the base of regular voluntary non-paid donations. This particular category of donations in the safest from the point of view of the prospect of having infectious diseases that can be transmitted through blood. Recrutitg and retaining the donors who make voluntary non-paid donations is a priority for the blood service on the way to achieving 100% voluntary non-paid donation of blood and its components. Blood transfusion service and its social component – donor ship must be the priority areas of the state policy because the results of its work are of paramount importance. The main task of the blood transfusion service is supply of high quality components for blood transfusion therapy. Quality of blood components is compliance of properties and specifications of the blood component supplied to the recipient with the set standards. Strict order of conformance with the approved regulations and procedures is important at all technological states and is a cornerstone of blood transfusion service products quality. All actions, planned and implemented, starting with planning donor ship and ending with the finished product manufacturing and storage conditions, are important for ensuring the quality as the final result.